An overview on how failure analysis contributes to flight safety in the Portuguese Air Force. (July 2016) - Duarte, Diogo; Marado, Bruno; Nogueira, João; Serrano, Bruno; Infante, Virgínia; Moleiro, Filipa
Abstract: Failure analysis has been, throughout the years, a fundamental tool used in the aerospace sector, supporting assessments performed by sustainment and design engineers mainly related to failure modes and material suitability. The predicted service life of aircrafts often exceeds 40 years, and the design assured life rarely accounts for all in service loads and in service environmental menaces that aging aircrafts must deal with throughout their service lives. From the most conservative safe-life conceptual design approaches to the most recent on-condition based design approaches, assessing the condition and predicting the failure modes of components and materials are essential for the development of adequate preventive and corrective maintenance actions as well as for the accomplishment and optimization of scheduled maintenance programs of aircrafts. Moreover, as the operational conditions of aircrafts may vary significantly from operator to operator (especially in military aircraft), it is necessary to access if the defined maintenance programs are adequate to guarantee the continuous reliability and safe usage of the aircrafts, preventing catastrophic failures which bear significant maintenance and repair costs, and that may lead to the loss of human lives. Thus being, failure analysis and material investigations performed as part of aircraft accidents and incidents investigations arise as powerful tools of the utmost importance for safety assurance and cost reduction within the aeronautical and aerospace sectors. The Portuguese Air Force (PRTAF) has operated different aircrafts throughout its long existence, and in some cases, has operated a particular type of aircraft for more than 30 years, gathering a great amount of expertise in: assessing failure modes of the aircrafts materials; conducting aircrafts accidents and incidents investigations (sometimes with the participation of the aircraft manufacturers and/or other operators); and in the development of design and repair solutions for in-service related problems. This paper addresses several studies to support the thesis that failure analysis plays a key role in flight safety improvement within the PRTAF. It presents a short summary of developed analysis and studies using optic and electronic (MEV) microscopy, material chemical composition analysis and Non Destructive Testing (NDT) to solve problems related to operation, maintenance and design issues. Additionally, it presents the investment that has been made by the Portuguese Air Force in the last two decades, to increase the flight safety through the implementation of powerful aircraft configuration management tools, and structural condition assessment methodologies based on strain measurements, NDT evaluation programs and, more recently, on Structural Health Monitoring systems in their fleets.